2016
DOI: 10.5935/1678-9741.20160085
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Valve Replacement: Treatment by Sternotomy versus Minimally Invasive Approach

Abstract: ObjectiveTo compare the results of aortic valve replacement with access by sternotomy or minimally invasive approach.MethodsRetrospective analysis of medical records of 37 patients undergoing aortic valve replacement by sternotomy or minimally invasive approach, with emphasis on the comparison of time of cardiopulmonary bypass and aortic clamping, volume of surgical bleeding, time of mechanical ventilation, need for blood transfusion, incidence of atrial fibrillation, length of stay in intensive care unit, tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…Recently, the number of cases with aortic pathology has increased markedly, which has resulted in the search for conservative surgical treatment methods [ 1 , 2 , 3 ]. Consequently, new minimally invasive approaches (e.g., upper and lower ministernotomy; V-shaped, Z-shaped, T-shaped, J-shaped sternotomy; and other types of ministernotomy) have been introduced [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the number of cases with aortic pathology has increased markedly, which has resulted in the search for conservative surgical treatment methods [ 1 , 2 , 3 ]. Consequently, new minimally invasive approaches (e.g., upper and lower ministernotomy; V-shaped, Z-shaped, T-shaped, J-shaped sternotomy; and other types of ministernotomy) have been introduced [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rst was that the study was observational, and patients were not randomized, so there were some age and weight differences between the MS and MT groups that could in uence the results. However, previous studies have not shown any difference in age and weight between MS and conventional full sternotomy for AVR [20][21][22]. The second limitation was that our study was under powered and was not su cient to de nitively reject the hypothesis that there was no correlation between MES count and development of delirium and cognitive decline.…”
Section: Limitationsmentioning
confidence: 78%
“…However, some authors have suggested that smaller incisions led to poor surgical led exposure, potentially making the surgery technically more demanding and with longer operative times [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors have suggested that smaller incisions led to poor surgical filed exposure, potentially making the surgery technically more demanding and with longer operative times [ 27 ].…”
Section: Discussionmentioning
confidence: 99%